Educational inequality - Yoshiaki Azuma; Herschel I. Grossman (Brown University, Department of Economics, 2001)
This paper develops a theoretical model of the inequality in wages and salaries associated with differences in years of schooling (educational inequality, for short). Our model assumes that in the long run individual decisions to become more educated equalize the lifetime earnings of more educated workers and comparable less educated workers. Given this assumption our model implies that innovations that increase the relative demand for more educated labor, and which cause short-run increases in educational inequality, in the long run induce offset- ting increases in the relative supply of more educated labor. But, our model also has the novel implication that innovations that increase differences between the wages and salaries received by workers with the same years of education who are more or less able (ability premiums, for short) cause a smaller fraction of workers to choose to become more educated. Consequently, innovations that increase ability premiums in the long run also cause educational inequality to be larger than otherwise. In applying our theory to recent changes in educational inequal- ity in the United States, we suggest that, to the extent that innovations that increase ability premiums are contributing to educational inequality, the increases in educational inequality during the 1980s and 1990s are unlikely to be soon reversed.
Keywords: D3; J3; O3; 330; Inequality; Education; Technology; Ability; Wages and Salaries; Bildung; Qualifikation; Bildungsertrag; Innovation; Lebenseinkommen; Theorie